A educação da criança surda com implante coclear : reflexões sobre a família, a clínica e a escola - Silva, Jaqueline Ahnert Siqueira da (2013)
The cochlear implant in our country is still considered a new practice, in particular with the deaf subject, because it is a recent procedure, which has been enabling, in a way, a hearing , often called by the media as bionic ear . The research aims at reflecting on the topic in order to understand more about that procedure that has been frequently carried out in Brazil. There has not been much research about this issue in the education field. Most of the data presented come from the clinical area. The implant possibility causes in the families of a deaf child the expectation of having a normal child and that anytime the child will be able to speak and hear. To achieve a good result, according to the speech specialists (audiologists), it is necessary that the child with the implant avoids contact with sign language and other people with hearing disability, which may compromise treatment. The study searches for analyzing the impacts of the cochlear implant in the life of a deaf child going to an Elementary School with a bilingual policy. The study uses as reference the historical-cultural perspective and considers the deaf is socially constituted, through the language, as cultural acquisition. It used the ethnographic study-case of a deaf child who had undergone surgery (cochlear implant). The field research was done through observation processes and semi-structures interviews. It attempts to comprehend the relation forms established between the child and the adults and other children in different spaces, as the child s home, the speech clinic, the school noting the repercussions from such relations the same way the child sees her/himself as the one with an implant. The study indicated that there are differences in the way the professionals understand the implanted children s condition and they relate with them in distinct ways. For some, the child is deaf and therefore, they prefer to use sign language when interacting. Others prioritize the orality, by considering that the implant can make the child able to hear and speak. Others even understand that an opportunity must be given to the child to learn the sign language and orality, in a way to broaden the child s possibilities of contact and interaction with others. That was also the mother s opinion. The analysis allows to see a child instructed regarding condition of an implanted child who is learning how to live with an implant. The child s testimonials provided evidence that the child recognizes her/himself as deaf and the sign language is the one that most fulfill her/his needs as a language user, however the opportunities brought by orality cannot be denied.